Increased Production of Tara (Caesalpinia spinosa) by Edaphoclimatic Variation in the Altitudinal Gradient of the Peruvian Andes. - Murga-Orrillo, Hipolito (2023)
Abstract: Tara production occurs mainly in the altitude gradient, where the edaphoclimatic conditions that affect the production of pods still need to be understood. The goal was to determine the altitudinal and edaphoclimatic effect on the production of tara pods in agroforestry and natural remnants in Cajamarca, Peru. Data analyses performed were the following: principal component analysis (PCA), regression analysis, the bootstrap method, and Pearson correlation analysis. For each 1 ◦C increase in temperature, the length and width of the pod decreased by 2.1 and 0.62 mm, and of the seed by 0.17 and 0.12 mm in the agroforestry environment; likewise, pod, valve, seed and gum weights were reduced by 23.9, 10.9, 13 and 2.3 g in the agroforestry environment, and 22.3, 13, 9.3 and 2.1 g in the natural environment. Activities such as association with annual crops and perennial pasture possibly favor the length and width of the pod and seed and the weight of the pod, valve, seed and gum in the agroforestry environment when compared to the natural environment. Larger pod and seed dimensions and higher pod, valve, seed and gum weights are related to higher soil CaCO3 contents in the natural environment and higher soil P and B contents in the agroforestry environment at higher altitudes. Higher Fe contents in the soil suggest an improvement in tara’s tannin weight (valve) in the natural and agroforestry environment. The effective response of tara, reflected in its weight and size of pods, was higher in an agroforestry environment than in a natural environment. Further studies on the production of tara pods are necessary for a better understanding of the interaction between altitude and soil fertility to expand the revenue and employment of Peruvian tara farmers.